Light‐Harvesting Antenna and Proton‐Activated Photodynamic Effect of a Novel BODIPY−Fullerene C60 Dyad as Potential Antimicrobial Agent. Issue 9 (10th April 2019) - Agazzi, Maximiliano L.; Durantini, Javier E.; Gsponer, Natalia S.; Durantini, Andrés M.; Bertolotti, Sonia G.; Durantini, Edgardo N.
Abstract: A covalently linked BODIPY−fullerene C60 dyad (BDP−C60 ) was synthesized as a two‐segment structure, which consists of a visible light‐harvesting antenna attached to an energy or electron acceptor moiety. This structure was designed to improve the photodynamic action of fullerene C60 to inactivate bacteria. The absorption spectrum of BDP−C60 was found to be a superposition of the spectra of its constitutional moieties, whereas the fluorescence emission of the BODIPY unit was strongly quenched by the fullerene C60 . Spectroscopic, calculations, and redox studies indicate a competence between photoinduced energy and electron transfer. Protonating the dimethylaminophenyl substituent through addition of an acidic medium led to a substantial increase in the fluorescence emission, triplet excited state formation, and singlet molecular oxygen production. At physiological pH, photosensitized inactivation of Staphylococcus aureus mediated by 1 μM BDP−C60 exhibited a 4.5 log decrease of cell survival (>99.997 %) after 15 min irradiation. A similar result was obtained with Escherichia coli using 30 min irradiation. Moreover, proton‐activated photodynamic action of BDP−C60 turned this dyad into a highly effective photosensitizer to eradicate E. coli . Therefore, BDP−C60 is an interesting photosensitizing structure in which the light‐harvesting antenna effect of the BODIPY unit combined with the protonation of dimethylaminophenyl group can be used to improve the photoinactivation of bacteria. Abstract : Photodynamic activity : A novel BODIPY−C60 dyad was designed to improve the photodynamic action of fullerene C60 . In this two segment structure, BODIPY acts as a visible light‐harvesting antenna, while C60 is a spin converter to produce 3 C60 * . In addition, proton‐activated photodynamic action of dyad turns this structure in a highly effective photosensitizer to eradicate microorganisms.